دراسة تحليلية لواقع إصابات العمل ومعاشات الشيخوخة في المؤسسة العامة للتأمينات الاجتماعية السورية خلال الفترة (2005-2012) - دريباتي, يسيرة (Latakia University Journal - Economic and Legal Sciences Series, 2018)
إن الاهتمام بموضوع الأخطار الاجتماعية يعني الاهتمام بالعنصر الفعّال في العملية الانتاجية، ألا وهو الانسان، وذلك بهدف تأمين الحماية له ولأفراد أسرته من بعده.يهدف البحث إلى تحليل واقع إصابات العمل ومعاشات الشيخوخة خلال الفترة الزمنية (2005-2012)، ثم إجراء مقارنة بين النفقات والإيرادات لكل من صندوق إصابات العمل وصندوق الشيخوخة والعجز والوفاة، وذلك للوقوف على الواقع الفعلي لهذين الصندوقين، وبيان إمكانية رفع التعويضات المختلفة، وتحسين أوضاع المتقاعدين والمستفيدين عموماً.بعد الدراسة والتحليل تم التوصل إلى ما يلي :- إن إصابات العمل تتطور بشكل متناقص خلال الفترة المدروسة.- إن معاشات الشيخوخة تتطور بشكل متزايد خلال الفترة المدروسة.- إن إيرادات صندوق إصابات العمل كافية لتغطية نفقاته، بالإضافة إلى تشكل فوائض سنوية في كافة سنوات الدراسة.- إن إيرادات صندوق الشيخوخة والعجز والوفاة تغطي نفقاته، باستثناء عام 2010 نتيجة .The interest in the social risks means the interest in human being who is the effective element in production process in order to protect him and his family after his deathThe research aims to analyze the reality of work injures and pensions during (2005-2010) and then to do a comparison between spendings and revenues for work injures insurance fund and old age-disability and death insurance fund in order to determine the actual fact of the two funds and the possibility of raising various compensations and improving the conditions of pensions and beneficiaries in general.After study and analysis it is reached to :- Work injures have decreased during the period of study- Pensions have increased during the period of study- Work injures fund are enough to cover its spendings in addition to have an annual surplus an all years of study- Revenues of old age-disability and death fund cover its spendings except the spendings in 2010.